INTEGRATION OF ISLAMIC BOARDING SCHOOL TRADITIONS AND FORMAL SCHOOLS: CURRICULUM STUDY AT SALSABILA ISLAMIC BOARDING SCHOOL, SAMARINDA - Lubis, Muhammad Rifai; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to understand the integration model of Islamic boarding school traditions with the formal education system implemented at the Salsabila Islamic Boarding School in Samarinda. This article analyzes how the Islamic-based Islamic boarding school curriculum is combined with the formal curriculum from the Ministry of Education and Culture, and its impact on the learning process and character formation of students. Using a descriptive qualitative approach, data was collected through interviews, participant observation and document analysis. The research results show that this integration creates harmony between Islamic traditions and modern educational needs, but there are still challenges in its implementation, such as limited learning tools.